Rebellion against Authority as the Essence of Existentialism in Harper Lee’s To Kill a Mockingbird - Yoan Nurbudhiati (Vivid: Journal of Language and Literature, 2015)
The aim of this article is to describe how individual existence can be achieved through rebellion against the authority figures which is projected in one of classic literary works, To Kill a Mockingbird by Harper Lee. In developing this research, the writer uses the approach of Existentialist philosophy in relation to the concept of Freedom and Authenticity coined by Jean Paul Sartre. Human being cast into the world inheritting his nature of freedom to choose his way of life, and to be an authentic human being, one must resist mass society’s doctrine of standardized human.  Through the analysis, the writer discovers that by acknowledging the freedom to choose, which in this case is rebelling against strict authority, the main character managed to hold her true authentic self and thus acclaming her existence. The rebellion by the main character in To Kill a Mockingbird portrays the main notion of Existentialism, how human being striving for his existence in the middle of intimidating universe.Keyword: Existentialism, Freedom,  Authenticity, Rebellion, Coming of age Literature